Evaluation of bioactivity and antibacterial properties of bioglass fabricated using a cellulose nano fibre template - Sarmast Shoushtari, Maryam; Leow, Yew Seng; Awang Biak, Dayang Radiah; Abdullah, Norhafizah; Alijantabar Aghouzi, Samaneh; Hoey, David; Kamarudin, Suryani; Zainuddin, Halimatun S. (Elsevier, 2023)
Past research in the bio-templating field has shown the positive impacts of the presence of Cellulose Nanofibre (CNF) as a template in the fabrication of bioactive glasses. SiO2“CaO“P2O5“Na2O bioactive glass (BG) was prepared and templated with CNF via the sol-gel method. The key aim of the approach is to demonstrate that the incorporation of templated bioglass with different percentages of CNF promotes apatite deposition on samples and maintains anti-bacterial properties. In this study, these glasses were exposed to a simulated body fluid (SBF) and phosphate buffer solution (PBS) for several periods to investigate in vitro bio-mineralization and biodegradation. To determine the hydroxyapatite (HA), samples were immersed in SBF under two treatments: no SBF refreshment or adjustment and refreshing SBF every 24 h to maintain a pH of 7.42. The result showed that the HA layer of samples without refreshment had better characterization than samples with a constant pH. The results of biodegradation revealed by increasing the percentage of template in bioglass structure, the chemical stability and the rate of degradation slightly increased across all time points.